A Printed Paper‐Based Anion Sensor Array for Multi‐Analyte Classification: On‐Site Quantification of Glyphosate. Issue 6 (31st March 2021) - Zhang, Zhoujie; Hamedpour, Vahid; Lyu, Xiaojun; Sasaki, Yui; Minami, Tsuyoshi
Abstract: We report a paper‐based chemosensor array device (PCSAD) for the quantitative detection of oxyanions including the herbicide glyphosate (GlyP) in aqueous media. The mechanism of the oxyanion detection relies on a coordination‐binding‐based sensor array. In this study, the competitive coordination binding among Zn 2+, four catechol dyes, and seven oxyanions caused noticeable colour changes. The colour changes were employed for qualitative and quantitative analyses using an in‐house automated image‐processing algorithm with pattern recognition for digital images. A linear discrimination analysis discerned similarly structured oxyanions with 100 % accuracy. The regression analysis allowed the accurate quantification of GlyP in the herbicide products with a limit of detection of 16 mg/L, which is lower than the health advisory value for children (20 mg/L) stipulated by the environmental protection agency (EPA). PCSAD is a powerful sensor device for the on‐site quantification of aqueous anions for environmental assessment. Abstract : Hip hip array ! A colourimetric chemosensor array on a paper‐based sensor device (PCSAD) allows for the quantification of oxyanions in aqueous media. The coordination‐binding‐based chemosensor array exhibited clear colour changes on the PCSAD, which allowed automatic image processing for pattern recognition. Importantly, the quantification of commercial herbicides in real samples was achieved by the proposed PCSAD.